تصور مشروع الشخصي للحياة لدى الطلاب الجامعين المتفائلين والمتشائمين - مزياني كريمة (University of Eloued جامعة الوادي, 2024)
Abstract: The clarity of the personal life project image for university students reflects the soundness of their pedagogical and psychological path, which is practically embodied in the presence of a strong motivation for achievement. Therefore, this research seeks to reveal the role played by both optimism and pessimism in the clarity and quality of the life project for students at the University of Moulay Mammar. This is done by studying the relationship and differences in these variables, which we identified through the optimism and pessimism scale by Dember et al. (1989) and the life project perception scale by researcher Zekoua Ahmed (2012). We have found results indicating that there is a clearer life project image for optimistic students who are characterized by a specific perception of their life goals, while pessimistic students show vagueness in their future life vision. We also found that males are clearer in their life project perception, and that medical students have a clearer life project perception compared to students in natural and life sciences and students in humanities and social sciences. وضوح صورة مشروع الشخصي للحياة لدى الطالب الجامعي تعكس سلامة المسار البيداغوجي والنفسي لديهم، والتي تتجسد عمليا في وجود دافعية قوية للإنجاز، وبالتالي يسعى هذا البحث للكشف عن الدور الذي يلعبه كل من التفاؤل والتشاؤم في وضوح ونوعية مشروع الحياة لدى طلبة جامعة مولود معمري، وذلك بدراسة العلاقة والفروق في هذه المتغيرات التي حددناها من خلال مقياس التفاؤل والتشاؤم لـ ديمبر وآخرون (1989) ومقياس تصور مشروع الحياة لباحث زقاوة احمد (2012). ولقد توصلنا إلى نتائج تشير إلى وجود صورة مشروع للحياة أكثر وضوحا لدى الطالب المتفائل والذي تميز بإدراك محدد لأهدافه في الحياة، وعكس الطالب المتشائم الذي أظهر ضبابية في رؤيته المستقبلية للحياة. ووجدنا أيضا أن الذكور أكثر وضوحا في تصور مشروعهم للحياة، كما انتهت النتائج لصالح طلبة تخصص الطب في تصورهم لمشروع الحياة مقارنة مع طلبة كلية العلوم الطبيعية والحياة وطلبة كلية العلوم الإنسانية والاجتماعية
دراسة ميدانية لطلاب جامعة مولود
Keywords: الطالب الجامعي; تصور مشروع الحياة; التفاؤل; التشاؤم; university student; life project perception; optimism; pessimism